RHEOLOGICAL PROPERTIES OF THE POLYURETHANE ADHESIVES - Palarczyková, Zuzana; Šiška, Bedřich; Machač, Ivan (My University, 2017)
In this contribution, the results of measurements are presented concerning rheological and mechanical properties of polyurethane adhesives used in the automotive industry. The work is focused on the determination of rheological characteristics of the individual components of polymeric adhesives tested and on rheological and mechanical properties of the adhesives in the hardening process. Experiments were performed with one type of the single-component adhesive and three types of two-component adhesives. All the components of PUR adhesives tested were viscoplastic with a certain degree of yield stress. The respective flow curves showed a shear-thinning and thixotropic behaviour; the results of oscillatory tests demonstrating that elastic behaviour dominated for all adhesive components. The elasticity of an adhesive evidently depended on their mixing ratio. Finally, it has been found out that adhesive gelation points measured in the hardening process could be detected much faster at a higher temperature than at a lower one.
Reologické vlastností polyuretanových lepidel
Keywords: polymeric adhesives; rheological properties; elasticity; gelation time; polymerní lepidla; reologické vlastnosti; elasticita; gelační cas